Medial collateral ligament reconstruction using bone-patellar tendon-bone allograft for chronic medial knee instability combined with multi-ligament injuries: a new technique. Issue 1 (December 2016) - Zheng, Xiaozuo; Li, Tong; Wang, Juan; Dong, Jiangtao; Gao, Shijun
Abstract Background The medial collateral ligament (MCL) is the main static stabilizer of the medial knee. The surgical treatment was recommended in cases with serious medial collateral ligament insufficiency combined with multi-ligament injuries and chronic symptomatic medial instability. Several surgical techniques have been described for the MCL reconstruction, while potential problems including donor site morbidity, complicated procedure, and high risk of femoral tunnel collision were reported. In order to minimize such potential limitations, we describe a new medial reconstruction technique for MCL injury using bone-patellar tendon-bone (BPTB) allograft. Methods A longitudinal incision at the medial knee was made. The centers of femoral and tibial attachments were gained through repeated isometricity test. Then, the bone grooves were made around the femoral and tibial centers. The appropriate BPTB allograft was selected, and both ends were trimmed. The prepared bone blocks were embedded into the grooves and fixed with cancellous screws. The programmed rehabilitation exercises were performed after the operation. Results A strong graft and bone-to-bone healing on both femoral and tibial attachment sites were obtained, and femoral tunnel collision during multi-ligament reconstruction was avoided. Satisfactory valgus and rotatory stability were gained. Conclusions This novel MCL reconstruction technique using BPTB allograft can be safely performed, and the clinical outcome was favorable with satisfactory valgus and rotatory stability. More cases and additional follow-up results are needed to verify the overall effect of this technique.